# mathematics

posted by .

Solve the following differential equation: (1 + x)*(dy/dx) = y

where y is a funtion of X

solve by the following by:

A)series expansion
B) elemantary method

please show working

## Respond to this Question

 First Name School Subject Your Answer

## Similar Questions

1. ### Mathematics

Solve the following differential equation, i.e. solve for y: dy/dx - y/x = 1/x + y + 1 I have this so far, 1. dy/dx= (y + 1 + xy + x)/x 2. x dy = (y + 1 + xy + x)dx 3. Integrate both sides... xy + c = xy + x + .5x^2y + .5x^2 + k where …
2. ### Mathematics

find the general solution of the following first order differential equation. dx/d(theta)=(xtan(theta))-(cos(theta)) show working
3. ### maths

please help find the general solution of the following first order differential equation. dx/dt = tx + 6t(exp)-t^2 pls show working
4. ### mathematics

find the general solution of the following first order differential equation. u(t): du/dt =(u/(t+2t)) pls show all working
5. ### maths

Solve the following differential equation: (1 + x)*(dy/dx) = y where y is a funtion of X solve by the following: A)series expansion B) elemantary method please show working
6. ### differential equations

Solve the following equation explicitly by expanding up to order x5, the following 2nd order diff equation. y''(x) = (1 + x^2)*y(x) pls show working y =f(x)
7. ### maths

Solve the following 2nd order differential equation explicitly by expanding up to order x5, y''(x) = (1 + x^2)*y(x) pls show working y =f(x)
8. ### maths

Solve the following differential equation: (1 + x)*(dy/dx) = y where y is a funtion of X solve by the following: A)series expansion B) elemantary method please show working
9. ### maths

Solve the following 2nd order differential equation explicitly by expanding up to order x5, y''(x) = (1 + x^2)*y(x) pls show working y =f(x)
10. ### PLEEEEEAAAASE HELP WITH DIFFERENTIAL EQ PROBLEMS!!

1) What are the equilibrium solutions to the differential equation and determine if it is stable or unstable with the initial condition y(-4)=1: 0.1(y+2)(4-y) 2) Use Euler's method with step size=0.5 and initial condition y(0)=3 to …

More Similar Questions